2017
DOI: 10.1308/rcsann.2017.0053
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory risk indicator for necrotising fasciitis (LRINEC) score for the assessment of early necrotising fasciitis: a systematic review of the literature

Abstract: INTRODUCTION Early operative debridement of necrotising fasciitis is a major outcome determinant. Identification and diagnosis of such patients can be clinically difficult. The Laboratory Risk Indicator for Necrotising Fasciitis (LRINEC) score first published in 2004 is based on routinely performed parameters and offers a method for identifying early cases. No literature review has yet been performed on the application of such a score. METHODS A systematic review of English-language literature was performed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
116
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 28 publications
11
116
1
12
Order By: Relevance
“…The patients in our study were older (median age 68 versus 56), exclusively from the ED, and had higher percentage of diabetes mellitus, peripheral vascular disease, and fever, compared to patients in the study of Wong et al Second, only patients with NF involving the limbs were included in our study, which might have biased the validation results. As previously mentioned, the LRINEC score of NF varied markedly depending on the affected body part, and the limbs had the lowest score of 6, compared to our average LINREC score of 5.3 [26]. Finally, the most common microorganism of monomicrobial necrotizing fasciitis in Europe and Singapore was Group A Streptococcus [5,11,20].…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…The patients in our study were older (median age 68 versus 56), exclusively from the ED, and had higher percentage of diabetes mellitus, peripheral vascular disease, and fever, compared to patients in the study of Wong et al Second, only patients with NF involving the limbs were included in our study, which might have biased the validation results. As previously mentioned, the LRINEC score of NF varied markedly depending on the affected body part, and the limbs had the lowest score of 6, compared to our average LINREC score of 5.3 [26]. Finally, the most common microorganism of monomicrobial necrotizing fasciitis in Europe and Singapore was Group A Streptococcus [5,11,20].…”
Section: Discussionsupporting
confidence: 47%
“…However, some studies have reported that the LRINEC score is a useful clinical tool with good performance for the diagnosis of NF [16,26]. One report retrospectively validated the LRINEC scores with an AUROC of 0.925, sensitivity of 76.3%, specificity of 93.1%, and positive and negative predictive values of 95.5% and 88.1% based on an LRINEC value of �6 to distinguish NF from severe cellulitis [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations